A hard carbon material and preparation method thereof, and sodium ion battery
By preparing hard carbon materials with specific particle size distribution and grading them with hard carbon particles with different particle size distribution, the problem of poor storage performance of existing hard carbon products in battery cell applications is solved, and the comprehensive effect of high compaction density, good first effect and excellent storage performance is achieved.
Patent Information
- Application Number
- CN202411968956.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-04-04
AI Technical Summary
The existing high-pressure hard carbon products have poor storage performance in battery cell applications, which is difficult to meet the comprehensive requirements of high compaction density, first-effect and storage performance of the negative electrode material at the battery cell end.
By providing a hard carbon material with a particle size distribution K90 greater than 1.9 and a particle size D01 ≥ 1.5 μm, a hard carbon material with high compaction density and good first effect is prepared.
It achieves high compaction density while maintaining good first-term effect and storage performance, ensuring that the battery cell still has good performance after storage.
Smart Images

Figure CN119764445A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of battery technology, and in particular to a hard carbon material and a preparation method thereof, and a sodium ion battery. Background Art
[0002] Hard carbon is a commonly used negative electrode material in sodium ion batteries. It has good conductivity and a large number of disordered defects and vacancies in its structure, which provide more active sites for sodium storage and doping modification sites for impurity elements. It has a large interlayer spacing and can show good structural stability during the sodium ion insertion and extraction process. As the negative electrode of sodium ion batteries, hard carbon has the advantages of good rate performance, high specific capacity, and stable cycle. In addition, hard carbon has a wide range of sources, a simple preparation process, and low cost, making it suitable for large-scale production.
[0003] In order to improve the energy density of sodium-ion batteries, downstream battery cell manufacturers have put forward high compaction or high gram capacity performance requirements for negative electrode materials. The common high compaction hard carbon products on the market have relatively high compaction density, but their initial efficiency is low and the storage performance in battery cell applications is poor, which is not conducive to their application in battery cells.
[0004] Therefore, there is an urgent need to launch high-density hard carbon products that can ensure that the materials have good initial effectiveness and storage performance.
[0005] Application Contents
[0006] In view of this, the present application provides a hard carbon and a preparation method thereof, and a sodium ion battery, aiming to improve the compaction density while maintaining good initial efficiency and storage performance in battery cell applications.
[0007] The embodiment of the present application is implemented by providing a hard carbon material, wherein the particle size distribution K90 of the hard carbon material is greater than 1.9, and the particle size D01 of the hard carbon material is ≥1.5 μm; wherein K90=(D90-D10) / D50.
[0008] In some embodiments, the particle size D50 of the hard carbon material is 4 to 16 μm; and / or the particle size Dmax of the hard carbon material is ≤40 μm; and / or the specific surface area of the hard carbon material is less than or equal to 4 m 2 / g; and / or, the compacted density of the hard carbon material is greater than 0.98g / cm 3 .
[0009] In some embodiments, the particle size distribution K90 of the hard carbon material is 2 to 2.5; and / or the particle size D50 of the hard carbon material is 6 to 8 μm; and / or the specific surface area of the hard carbon material is less than or equal to 3 m 2 / g; and / or, the compacted density of the hard carbon material is greater than 1g / cm 3 .
[0010] Correspondingly, an embodiment of the present application also provides a method for preparing a hard carbon material, comprising: providing a first hard carbon particle and a second hard carbon particle; grading the first hard carbon particle and the second hard carbon particle to obtain a hard carbon material; wherein the ratio of the particle size D50 of the first hard carbon particle to the particle size D50 of the second hard carbon particle is greater than or equal to 2, the particle size distribution K90 of the first hard carbon particle satisfies: 0.5<K90<1.5, and the particle size distribution K90 of the second hard carbon particle satisfies: 0.5<K90<1.5.
[0011] In some embodiments, the ratio of the particle size D50 of the first hard carbon particles to the particle size D50 of the second hard carbon particles is 2 to 8; and / or the particle size D50 of the second hard carbon particles is 3 to 10 μm; and / or the particle size distribution K90 of the first hard carbon particles satisfies: 0.9≤K90≤1.45; and / or the particle size distribution K90 of the second hard carbon particles satisfies: 0.9≤K90≤1.45.
[0012] In some embodiments, the mass ratio of the first hard carbon particles to the second hard carbon particles is 1:3 to 3:1.
[0013] In some embodiments, providing the first hard carbon particles and the second hard carbon particles comprises:
[0014] Providing a first hard carbon precursor, washing it with acid and water until the pH is 6±1; then carbonizing it under an inert atmosphere to obtain the first hard carbon particles; and,
[0015] A second hard carbon precursor is provided, and is acid-washed and water-washed until the pH value is 6±1; and then carbonized under an inert atmosphere to obtain the second hard carbon particles.
[0016] The carbonization temperature is 1000-1700° C.; and / or,
[0017] The carbonization time is 2 to 5 hours; and / or,
[0018] The inert atmosphere is an atmosphere formed by one or more of nitrogen, helium, neon, argon, krypton, xenon, and radon; and / or,
[0019] The pickling solution used in the pickling comprises a mixed acid formed by one or more of a hydrochloric acid solution, a sulfuric acid solution, and a nitric acid solution; and / or,
[0020] In the pickling, the mass ratio of the hard carbon precursor to be pickled to the pickling liquid is 1:
[0021] (2~10).
[0022] In some embodiments, the hard carbon precursor having the first particle size distribution and the hard carbon precursor having the second particle size distribution are obtained by crushing the same hard carbon precursor; and / or,
[0023] The first hard carbon precursor includes one or more of a biomass-based precursor, a resin-based precursor and a pitch-based precursor; and / or,
[0024] The second hard carbon precursor includes one or more of a biomass-based precursor, a resin-based precursor, and a pitch-based precursor.
[0025] Correspondingly, an embodiment of the present application also provides a sodium ion battery, comprising the above-mentioned hard carbon material.
[0026] The particle size distribution K90 of the hard carbon material of the present application is greater than 1.9, and the particle size D01 of the hard carbon material is ≥1.5μm; wherein K90=(D90-D10) / D50. The hard carbon material in this embodiment has a wide particle size distribution and a small proportion of small-size particles, which can avoid the influence of fine particles on the initial efficiency and post-storage performance of the battery. While having a high compaction density, it can also maintain a good initial efficiency, and when applied to the battery cell, it still has good performance after storage. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For those skilled in the art, other drawings can be obtained based on these drawings without creative work.
[0028] Figure 1 A schematic diagram of a process for preparing a hard carbon material according to an embodiment of the present invention;
[0029] Figure 2 is a SEM image of the hard carbon material prepared in Example 1;
[0030] Figure 3 This is the SEM image of the hard carbon material prepared in Comparative Example 2. DETAILED DESCRIPTION
[0031] The technical solutions in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, rather than all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by those skilled in the art without making creative work belong to the scope of protection of the present application. In addition, it should be understood that the specific implementation methods described herein are only used to illustrate and explain the present application and are not used to limit the present application. In the present application, unless otherwise stated, the directional words used, such as "upper" and "lower", are specifically the directions of the drawings in the accompanying drawings. In addition, in the description of the present application, the term "including" means "including but not limited to".
[0032] Various embodiments of the present application may be presented in the form of a range; it should be understood that the description in the form of a range is only for convenience and brevity, and should not be understood as a rigid limitation on the scope of the present application; therefore, the range description should be considered to have specifically disclosed all possible sub-ranges and single numerical values within the range. For example, the range description from 1 to 6 should be considered to have specifically disclosed sub-ranges, such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., as well as single numbers within the range, such as 1, 2, 3, 4, 5 and 6, which apply regardless of the range. In addition, whenever a numerical range is indicated herein, it is meant to include any cited number (fractional or integer) within the indicated range.
[0033] In this application, "and / or" describes the association relationship of associated objects, indicating that there may be three relationships. For example, A and / or B can mean: A exists alone, A and B exist at the same time, and B exists alone. A and B can be singular or plural.
[0034] In the present application, "at least one" means one or more, and "plurality" means two or more. "At least one", "at least one of the following" or similar expressions refer to any combination of these items, including any combination of single items or plural items. For example, "at least one of a, b, or c", or "at least one of a, b, and c" can all mean: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, c can be single or multiple, respectively.
[0035] The compaction density of currently available hard carbon materials is generally low. Taking biomass-based hard carbon as an example, its compaction density is usually 0.95g / cm 3The commonly used high-compacted hard carbon products on the market have a relatively high high-compacted density, but their initial efficiency is low and their storage performance in battery cell applications is poor. The relevant research involved in this application found that this may be due to the high content of fine powder in the hard carbon material.
[0036] Based on this, the present application provides a hard carbon material that can improve the compaction density, has good initial effect and good storage performance in battery cell applications. The capacity retention rate and capacity recovery rate after storage in the battery cell are good, that is, the battery cell still has good performance after storage.
[0037] In some embodiments, the particle size distribution K90 of the hard carbon material is greater than 1.9, and has a wide particle size distribution. Further, K90 may satisfy 1.9<K90≤3, specifically 1.9<K90≤2.8, 1.9≤K90≤2.5, 2.0≤K90≤2.5.
[0038] Among them, K90 = (D90-D10) / D50, D10 represents the particle size corresponding to when the cumulative particle size distribution percentage in the sample reaches 10%; D50 is also called the median diameter or median particle size, which represents the particle size corresponding to when the cumulative particle size distribution percentage in the sample reaches 50%; D90 represents the particle size corresponding to when the cumulative particle size distribution percentage in the sample reaches 90%.
[0039] Furthermore, the particle size D01 of the hard carbon material is ≥1.5 μm, and specifically can be 1.5-1.7 μm, 1.7-1.8 μm, 1.8-2.0 μm, 1.8-2.5 μm, etc.
[0040] The hard carbon material in this embodiment has a wide particle size distribution and a small proportion of small particle size particles, which can avoid the impact of fine particles on the initial efficiency and post-storage performance of the battery. While having a high compaction density, it can also maintain a good initial efficiency, and when applied to the battery cell, it still has good performance after storage.
[0041] In some embodiments, the particle size D50 of the hard carbon material is 4 to 16 μm, specifically 4 to 12 μm, 5 to 12 μm, 5 to 10 μm, 6 to 8 μm, etc.
[0042] Furthermore, in some embodiments, the particle size Dmax of the hard carbon material is ≤40 μm, and can be specifically 35-40 μm, 30-35 μm, 25-30 μm, 20-25 μm, etc.
[0043] In some embodiments, the specific surface area of the hard carbon material is less than or equal to 4 m 2 / g, specifically less than or equal to 3m 2 / g, for example, 3 to 4 m2 / g, 2.8~3m 2 / g, 2.5~2.8m 2 / g, 2.2~2.5m 2 / g, 2.0~2.2m 2 / g, etc.
[0044] In one embodiment, the compacted density of the hard carbon material is greater than 0.98 g / cm 3 Preferably, the compacted density can be greater than or equal to 1g / cm 3 , for example, it can be 1.0281 g / cm 3 or 1.0204 g / cm 3 The compaction density of the hard carbon material of this embodiment is relatively high. Compared with conventional hard carbon materials, its compaction density is slightly increased, and this slightly increased compaction density can significantly increase the energy density.
[0045] In one embodiment, the hard carbon material is formed by mixing two or more hard carbon particles, including first hard carbon particles and second hard carbon particles. The first hard carbon particles and the second hard carbon particles can refer to the relevant description of the preparation method of the hard carbon material provided in this application.
[0046] Correspondingly, the present application provides a method for preparing a hard carbon material, see Figure 1 , Figure 1 1 is a flow chart of an embodiment of a method for preparing hard carbon provided by the present application, comprising the following steps:
[0047] Step S11: providing first hard carbon particles and second hard carbon particles;
[0048] Step S12: grading the first hard carbon particles and the second hard carbon particles to obtain a hard carbon material.
[0049] In the step S11:
[0050] The ratio of the particle size D50 of the first hard carbon particles to the particle size D50 of the second hard carbon particles is greater than or equal to 2, and may further be in the range of 2 to 8, specifically 2 to 6, 4 to 6, 4 to 5, etc.
[0051] Furthermore, the particle size D50 of the second hard carbon particles is 3 to 10 μm, specifically 3 to 8 μm, 5 to 8 μm, 5 to 6 μm, etc.
[0052] Specifically, the particle size distribution K90 of the first hard carbon particles and the second hard carbon particles both satisfy: 0.5<K90<1.5, for example, 0.5<K90≤1.2, 0.8<K90≤1.2, 1.0<K90≤1.2, etc.
[0053] In some embodiments, both the first hard carbon particles and the second hard carbon particles undergo a purification process, and the purification process includes pickling; in some embodiments, the purification process includes pickling and water washing until the pH is 6±1. The pickling solution used for pickling includes a mixed acid formed by one or more of hydrochloric acid solution, sulfuric acid solution, nitric acid solution, and hydrofluoric acid solution. The concentration of the pickling solution is 1 to 10 mol / L, specifically 1 mol / L, 2 mol / L, 3 mol / L, 5 mol / L, 8 mol / L, 10 mol / L, etc. The solid-liquid mass ratio of the pickling can be 1: (2 to 10), specifically 1: 2, 1: 5, 1: 8, 1: 10, etc. The pickling temperature can be 15 to 80°C, and the pickling time can be 1 to 10 hours.
[0054] In a specific embodiment, the providing of the first hard carbon particles includes preparing the first hard carbon particles, specifically including: providing a first hard carbon precursor, acid washing and water washing to a pH of 6±1, and then carbonizing to obtain the first hard carbon particles. Further, the particle size distribution of the first precursor can be consistent with the particle size distribution of the first hard carbon particles.
[0055] In a specific embodiment, the providing of the second hard carbon particles includes preparing the second hard carbon particles, which includes: providing a second hard carbon precursor, washing with acid and water until the pH is 6±1, and then carbonizing to obtain the second hard carbon particles. Further, the particle size distribution of the second precursor can be consistent with the particle size distribution of the second hard carbon particles.
[0056] The carbonization temperature may be 1000-1700°C, the carbonization time may be 2-5 hours, and the carbonization atmosphere may be an inert atmosphere. It is understandable that, unless otherwise specified, the inert gas involved in this application is mainly used to isolate oxygen, and may be specifically selected from one or more of nitrogen, helium, neon, argon, krypton, xenon, and radon.
[0057] In the above embodiment, by purifying and carbonizing the first hard carbon precursor and the second hard carbon precursor respectively by acid washing, each of the first hard carbon particles and the second hard carbon particles can have a good pore structure and surface structure. After mixing at their respective corresponding particle size distributions, the graded hard carbon material can have a high compaction density while maintaining a high capacity and initial efficiency, and when applied to the battery cell, it still has good performance after storage.
[0058] In some embodiments, the first hard carbon precursor and the second hard carbon precursor may each independently include one or more of a biomass-based precursor, a resin-based precursor, and an asphalt-based precursor. The biomass-based precursor includes one or more of coconut shells, walnut shells, straw, bamboo, sugar, fruit shells, and lignin; the resin-based precursor includes one or more of phenolic resin, polyester resin, epoxy resin, polyformaldehyde resin, urea-formaldehyde resin, furfural resin, furfural ketone resin, acrylic resin, polyamide, polyimide, and polyvinyl alcohol; the asphalt-based precursor includes one or more of coal tar and petroleum asphalt.
[0059] In some embodiments, the first hard carbon precursor and the second hard carbon precursor may be made of the same material, but have different particle size distributions. Specifically, the first hard carbon precursor and the second hard carbon precursor may be obtained by crushing the same hard carbon precursor.
[0060] In step S12:
[0061] The mass ratio of the first hard carbon particles and the second hard carbon particles in grading is (1:3) to (3:1), specifically (1:3) to (1:2), (1:2) to (1:1), (1:1) to (2:1), (2:1) to (3:1), (2:3) to (3:2), (2:3) to (1:1), (1:1) to (3:2), etc.
[0062] Specifically, the grading may be to uniformly mix the first hard carbon particles and the second hard carbon particles.
[0063] In this embodiment, by providing large particles and small particles with a large difference in D50, and both the large particles and the small particles have a K90 value with a narrow particle size distribution, the compaction density of the hard carbon material can be improved after grading, and it has a better first effect. When applied to the battery cell, it still has good performance after storage.
[0064] The present application also provides a sodium ion battery negative electrode material, wherein the sodium ion battery hard carbon negative electrode material comprises the hard carbon material provided in the present application, or the sodium ion battery hard carbon negative electrode material comprises the material prepared by the preparation method provided in the present application.
[0065] Furthermore, the present application also provides a sodium ion battery, which includes the sodium ion battery negative electrode material provided in the present application.
[0066] Taking coconut shell biomass raw materials as a hard carbon precursor as an example, the technical scheme and technical effects of the present application are described in detail through specific embodiments, comparative examples and experimental examples. The following embodiments are only some embodiments of the present application and do not specifically limit the present application.
[0067] Example 1
[0068] This embodiment provides a hard carbon material and a preparation method thereof, and the preparation steps are as follows:
[0069] Step 1: Crush the biomass raw materials to D50 = 4.5 μm, D10 = 2 μm, K90 = 1.2 as small particles for later use, and crush them to D50 = 15 μm, D10 = 8 μm, K90 = 1.2 as large particles for later use. ;
[0070] Step 2: Use a mixed acid of hydrochloric acid and sulfuric acid (concentration 5 mol / L, molar ratio of hydrochloric acid to sulfuric acid 1:1) for pickling. The weight ratio of the raw material to the acid solution after crushing is 1:5. After pickling, wash with water repeatedly and filter press until the pH is 6±1, and dry the material after filtration.
[0071] Step 3: The dried large and small particle samples are subjected to high-temperature carbonization sintering respectively, with the sintering temperature being 1250°C and the sintering time being 3.5h.
[0072] Step 4: Use a high-speed mixer to mix the large particles and small particles in a mass ratio of 6:4 to obtain the final hard carbon material.
[0073] Example 2
[0074] This embodiment provides a hard carbon material and a preparation method thereof, comprising the following steps:
[0075] Step 1: Crush the biomass raw materials to D50=3.5μm, D10=1.7μm, K90=1.2 as small particles for later use; crush them to D50=13μm, D10=8μm, K90=1.2 as large particles for later use.
[0076] Step 2: Use a mixed acid of hydrochloric acid and sulfuric acid (concentration 5 mol / L, molar ratio of hydrochloric acid to sulfuric acid 1:1) for pickling. The weight ratio of the raw material to the acid solution after crushing is 1:5. After pickling, wash with water repeatedly and filter press until the pH is 6±1, and dry the material after filtration.
[0077] Step 3: The dried large and small particle samples are subjected to high-temperature carbonization sintering respectively, with the sintering temperature being 1250°C and the sintering time being 3.5h.
[0078] Step 4: Use a high-speed mixer to mix the large particles and small particles in a mass ratio of 1:1 to obtain the final hard carbon material.
[0079] Example 3
[0080] This embodiment provides a hard carbon and a preparation method thereof, comprising the following steps:
[0081] Step 1: Crush the biomass raw materials to D50=4.5μm, D10=2μm, K90=1.3 as small particles for later use, and crush them to D50=15, D10=6, K90=1.45 as large particles for later use.
[0082] Step 2: Use a mixed acid of hydrochloric acid and sulfuric acid (concentration 5 mol / L, molar ratio of hydrochloric acid to sulfuric acid 1:1) for pickling. The weight ratio of the raw material to the acid solution after crushing is 1:5. After pickling, wash with water repeatedly and filter press until the pH is 6±1, and dry the material after filtration.
[0083] Step 3: The dried large and small particle samples are subjected to high-temperature carbonization sintering respectively, with the sintering temperature being 1250°C and the sintering time being 3.5h.
[0084] Step 4: Use a high-speed mixer to mix the large particles and small particles in a mass ratio of 6:4 to obtain the final hard carbon material.
[0085] Example 4
[0086] This embodiment provides a hard carbon and a preparation method thereof, comprising the following steps:
[0087] Step 1: Crush the biomass raw materials to D50=3μm, D10=1.6μm, K90=0.7 as small particles for later use; crush them to D50=8μm, D10=3μm, K90=0.9 as large particles for later use.
[0088] Step 2: Use a mixed acid of hydrochloric acid and sulfuric acid (concentration 5 mol / L, molar ratio of hydrochloric acid to sulfuric acid 1:1) for pickling. The weight ratio of the raw material to the acid solution after crushing is 1:5. After pickling, wash with water repeatedly and filter press until the pH is 6±1, and dry the material after filtration.
[0089] Step 3: The dried large and small particle samples are subjected to high-temperature carbonization sintering respectively, with the sintering temperature being 1250°C and the sintering time being 3.5h.
[0090] Step 4: Use a high-speed mixer to mix the large particles and small particles in a mass ratio of 1:1 to obtain the final hard carbon material.
[0091] Example 5
[0092] This embodiment provides a hard carbon and a preparation method thereof, comprising the following steps:
[0093] Step 1: Crush the biomass raw materials to D50=6μm, D10=2.7μm, K90=1.0 as small particles, and crush them to D50=25μm, D10=10μm, K90=0.8 as large particles.
[0094] Step 2: Use a mixed acid of hydrochloric acid and sulfuric acid (concentration 5 mol / L, molar ratio of hydrochloric acid to sulfuric acid 1:1) for pickling. The weight ratio of the raw material to the acid solution after crushing is 1:5. After pickling, wash with water repeatedly and filter press until the pH is 6±1, and dry the material after filtration.
[0095] Step 3: The dried large and small particle samples are subjected to high-temperature carbonization sintering respectively, with the sintering temperature being 1250°C and the sintering time being 3.5h.
[0096] Step 4: Use a high-speed mixer to mix the large particles and small particles in a mass ratio of 4:6 to obtain the final hard carbon material.
[0097] Example 6
[0098] This embodiment provides a hard carbon and a preparation method thereof, comprising the following steps:
[0099] Step 1: Crush the biomass raw materials to D50=4.5μm, D10=2μm, K90=1.2 as small particles for later use; crush them to D50=15μm, D10=8μm, K90=1.2 as large particles for later use.
[0100] Step 2: Use hydrochloric acid solution (concentration 5 mol / L) as acid solution for pickling. The weight ratio of the raw material to the acid solution after crushing is 1:5. After pickling, wash with water repeatedly and filter press until the pH is 6±1, and dry the material after filter press.
[0101] Step 3: The dried large and small particle samples are subjected to high-temperature carbonization sintering respectively, with the sintering temperature being 1250°C and the sintering time being 3.5h.
[0102] Step 4: Use a high-speed mixer to mix the large particles and small particles in a mass ratio of 6:4 to obtain the final hard carbon material.
[0103] Comparative Example 1
[0104] This comparative example provides a hard carbon material and a preparation method thereof, comprising the following steps:
[0105] Step 1: Crush the biomass raw materials to D50=4.5μm, D10=2μm, K90=1.2 as small particles, and crush them to D50=11μm, D10=7μm, K90=1.05 as large particles.
[0106] Step 2: Use a mixed acid of hydrochloric acid and sulfuric acid (concentration 5 mol / L, molar ratio of hydrochloric acid to sulfuric acid 1:1) for pickling. The weight ratio of the raw material to the acid solution after crushing is 1:5. After pickling, wash with water repeatedly and filter press until the pH is 6±1, and dry the material after filtration.
[0107] Step 3: The dried large and small particle samples are subjected to high-temperature carbonization sintering respectively, with the sintering temperature being 1250°C and the sintering time being 3.5h.
[0108] Step 4: Use a high-speed mixer to mix the large particles and small particles in a mass ratio of 6:4 to obtain the final hard carbon material.
[0109] Comparative Example 2
[0110] This comparative example provides a hard carbon material and a preparation method thereof, comprising the following steps:
[0111] Step 1: Crush the biomass raw materials to D50 = 6 μm, D10 = 2 μm, and K90 = 1.45.
[0112] Step 2: Use a mixed acid of hydrochloric acid and sulfuric acid (concentration 5 mol / L, molar ratio of hydrochloric acid to sulfuric acid 1:1) for pickling. The weight ratio of the raw material to the acid solution after crushing is 1:5. After pickling, wash with water repeatedly and filter press until the pH is 6±1, and dry the material after filtration.
[0113] Step 3: The dried sample is subjected to high-temperature carbonization sintering at a sintering temperature of 1250°C and a sintering time of 3.5 h to obtain a finished hard carbon.
[0114] Comparative Example 3
[0115] This comparative example provides a hard carbon material and a preparation method thereof, comprising the following steps:
[0116] Step 1: Crush the biomass raw materials to D50=4.5μm, D10=2μm, K90=1.5 as small particles for later use; crush them to D50=15μm, D10=4μm, K90=1.5 as large particles for later use.
[0117] Step 2: Use a mixed acid of hydrochloric acid and sulfuric acid (concentration 5 mol / L, molar ratio of hydrochloric acid to sulfuric acid 1:1) for pickling. The weight ratio of the raw material to the acid solution after crushing is 1:5. After pickling, wash with water repeatedly and filter press until the pH is 6±1, and dry the material after filtration.
[0118] Step 3: The dried large and small particle samples are subjected to high-temperature carbonization sintering respectively, with the sintering temperature being 1250°C and the sintering time being 3.5h.
[0119] Step 4: Use a high-speed mixer to mix the large particles and small particles in a mass ratio of 6:4 to obtain the final hard carbon material.
[0120] The prepared hard carbon materials are subjected to corresponding tests, including physicochemical properties and related performance tests after forming batteries.
[0121] 1 - Particle size test
[0122] It is detected by a Malvern 3000 model laser particle size analyzer to obtain K90, D01, and D50. The test results are shown in Table 1.
[0123] 2 - Tap density detection
[0124] It is tested by a tap density meter of Yuanneng Technology, and the tap density is measured at 150 MPa. The test results are shown in Table 1
[0125] 3 - Specific surface area
[0126] The specific surface area is tested according to the method described in the standard <GBT 19587 - 2017 Determination of Specific Surface Area of Solid Substances by Gas Adsorption BET Method>. The test results are shown in Table 1.
[0127] 4 - Scanning electron microscopy SEM
[0128] The hard carbon materials of Example 1 and Comparative Example 2 are subjected to SEM tests. Refer to Figure 2 and Figure 3 , Figure 2 is the SEM image of the hard carbon material prepared in Example 1, Figure 3 is the SEM image of the hard carbon material prepared in Comparative Example 2.
[0129] 5 - Preparation of coin - type half - cell and performance testing
[0130] Take the hard carbon materials prepared in the above - mentioned examples and comparative examples, homogenize, coat, dry, and punch them into circular electrodes with a diameter of 8 mm according to the ratio of HC:PVDF:SP = 92:4:4. Use sodium foil as the counter electrode and a mixed solution of 1 mol / L NaPF6 and ethylene carbonate (EC):dimethyl carbonate (DEC) = 1:1 vol.% as the electrolyte to make a CR2025 coin - type battery.
[0131] The test conditions are as follows: for the first charge - discharge test, discharge at 0.1C (nominal capacity 200 mA / g) to 0V, and then charge to 2.5V to obtain the first discharge capacity, the first charge gram capacity, and the first efficiency; the test results are shown in Table 1.
[0132] 6 - Preparation of soft - pack battery cells and performance testing
[0133] Take the hard carbon materials prepared in the above - mentioned examples and comparative examples and combine them with sodium - based layered oxides to prepare an 8Ah soft - pack battery cell. The specific steps are as follows. Test the electrode compaction and the storage performance of the battery cell. The test results are shown in Table 2.
[0134] Step 1: Use the hard carbon A, B, and C corresponding to Example 1, and mix them according to the mass ratio of hard carbon HC: sodium carboxymethyl cellulose (CMC): conductive carbon black (SP): styrene-butadiene rubber (SBR) = 93.9:1.5:2:2.6, wherein the hard carbon main material is 5 kg, and slurry is performed in a vacuum planetary mixer, and deionized water is added to adjust the slurry viscosity to 3000-5000 mPa·s;
[0135] Step 2: According to the mass ratio of layered oxide: polyvinylidene fluoride (PVDF): conductive carbon black (SP): carbon nanotube (CNT) = 95.8:2:1.6:0.6, wherein the layered oxide main material feed is 5 kg, the positive electrode is homogenized in a vacuum planetary mixer, and NMP is added to adjust the slurry viscosity to 3000-5000 mPa·s;
[0136] Step 3: Using 12μm aluminum foil as the base, apply the positive electrode slurry on the aluminum foil to ensure that the single-sided surface density is 13g / m 2 ;
[0137] Step 4: Using 8 μm copper foil as the base, different hard carbon slurries were coated on the copper foil to ensure that the NP ratio (ratio of negative electrode capacity to positive electrode capacity) with the positive electrode was 1.1;
[0138] Step 5: Through the subsequent process, the electrode die-cut laminations are assembled and injected with electrolyte (the volume ratio of the electrolyte is EC (ethylene carbonate): PC (propylene carbonate) = 1:1, and the concentration of NaPF6 is 1 mol / L;) and the battery cell is packaged and divided into components to prepare a battery cell with a capacity of 8Ah.
[0139] Test: After the capacity division is completed, the battery cell is charged and discharged three times at 1C at room temperature to fix the capacity. The average value of the three discharges is taken as the initial capacity A1. After the battery cell is fully charged at room temperature, the fully charged battery cell is placed in a high temperature box at 45°C for 7 days and then taken out for 1C discharge. The discharge capacity is recorded as A2. The battery cell is charged and discharged three times at 1C again. The average discharge capacity of the three cycles is recorded as A3. The capacity retention rate = A2 / A1, and the capacity recovery rate = A3 / A1.
[0140] Table 1
[0141]
[0142]
[0143] Table 2
[0144]
[0145] It can be seen from Table 1 and Table 2 that:
[0146] Compared with Comparative Examples 1-3, the hard carbon materials of Examples 1-6 have a high compaction density (greater than 0.95 g / cm 3 ), while maintaining a relatively high gram capacity and initial efficiency, and when applied to the battery cell, it can still have a good capacity retention rate and capacity recovery rate after storage, that is, the performance after storage is still good.
[0147] Although the hard carbon material in Comparative Example 2 has compacted density, its initial efficiency is greatly reduced. Figure 2 and Figure 3 ) It can be seen that there is more fine powder of the hard carbon material in Comparative Example 2, which can improve the compaction density to a certain extent, but the presence of fine powder also has a certain negative impact on the initial effect of the hard carbon material and the capacity retention and capacity recovery after storage at the battery cell end.
[0148] It can be seen from Example 1 and Example 6 that, compared with pickling with a single hydrochloric acid solution, pickling with a mixed acid can further increase the compaction density of the final hard carbon material after grading.
[0149] From the above content, it can be seen that in this application, the large particle and small particle grading that meets specific conditions can have a significant impact on the compaction density and corresponding properties of the final hard carbon material, and can achieve a higher compaction while ensuring the initial effect and of the material.
[0150] The hard carbon and its preparation method, and the sodium ion battery provided in the embodiments of the present application are introduced in detail above. Specific examples are used in this article to illustrate the principles and implementation methods of the present application. The description of the above embodiments is only used to help understand the method of the present application and its core idea; at the same time, for technical personnel in this field, according to the idea of the present application, there will be changes in the specific implementation method and application scope. In summary, the content of this specification should not be understood as a limitation on the present application.
Claims
1. A hard carbon material, characterized in that: The particle size distribution K90 of the hard carbon material is greater than 1.9, and the particle size D01 of the hard carbon material is ≥1.5 μm; wherein K90=(D90-D10) / D50.
2. The hard carbon material according to claim 1, characterized in that The particle size D50 of the hard carbon material is 4 to 16 μm; and / or, The particle size Dmax of the hard carbon material is ≤40 μm; and / or, The specific surface area of the hard carbon material is less than or equal to 4 m 2 / g; and / or, The compacted density of the hard carbon material is greater than 0.98 g / cm 3 .
3. The hard carbon material according to claim 2, characterized in that The particle size distribution K90 of the hard carbon material is 2 to 2.5; and / or, The particle size D50 of the hard carbon material is 6 to 8 μm; and / or, The specific surface area of the hard carbon material is less than or equal to 3 m 2 / g; and / or, The compacted density of the hard carbon material is greater than 1 g / cm 3 .
4. A method for preparing a hard carbon material, characterized in that: include: providing first hard carbon particles and second hard carbon particles; grading the first hard carbon particles and the second hard carbon particles to obtain a hard carbon material; The ratio of the particle size D50 of the first hard carbon particles to the particle size D50 of the second hard carbon particles is greater than or equal to 2, the particle size distribution K90 of the first hard carbon particles satisfies: 0.5<K90<1.5, and the particle size distribution K90 of the second hard carbon particles satisfies: 0.5<K90<1.
5.
5. The preparation method according to claim 4, characterized in that: The ratio of the particle size D50 of the first hard carbon particles to the particle size D50 of the second hard carbon particles is 2 to 8; and / or, The particle size D50 of the second hard carbon particles is 3 to 10 μm; and / or, The particle size distribution K90 of the first hard carbon particles satisfies: 0.9≤K90≤1.45; and / or, The particle size distribution K90 of the second hard carbon particles satisfies: 0.9≤K90≤1.
45.
6. The preparation method according to claim 4 or 5, characterized in that: The mass ratio of the first hard carbon particles to the second hard carbon particles is 1:3 to 3:
1.
7. The preparation method according to any one of claims 4 to 6, characterized in that: The providing of the first hard carbon particles and the second hard carbon particles comprises: Providing a first hard carbon precursor, washing it with acid and water until the pH is 6±1; then carbonizing it under an inert atmosphere to obtain the first hard carbon particles; and, A second hard carbon precursor is provided, and is acid-washed and water-washed until the pH value is 6±1; and then carbonized under an inert atmosphere to obtain the second hard carbon particles.
8. The preparation method according to claim 7, characterized in that: The carbonization temperature is 1000-1700° C.; and / or, The carbonization time is 2 to 5 hours; and / or, The inert atmosphere is an atmosphere formed by one or more of nitrogen, helium, neon, argon, krypton, xenon, and radon; and / or, The pickling solution used in the pickling includes a mixed acid formed by one or more of hydrochloric acid solution, sulfuric acid solution, nitric acid solution and hydrofluoric acid solution; and / or, The solid-liquid mass ratio of the pickling is 1:(2-10); and / or, The pickling temperature is 15 to 80° C. and the time is 1 to 10 hours.
9. The preparation method according to claim 7, characterized in that: The first hard carbon precursor and the second hard carbon precursor are obtained by crushing the same hard carbon precursor; and / or, The first hard carbon precursor includes one or more of a biomass-based precursor, a resin-based precursor and a pitch-based precursor; and / or, The second hard carbon precursor includes one or more of a biomass-based precursor, a resin-based precursor, and a pitch-based precursor.
10. A sodium ion battery, characterized in that: The hard carbon material comprises the hard carbon material according to any one of claims 1 to 3, or the hard carbon material prepared by the method for preparing the hard carbon material according to any one of claims 4 to 9.